Impact of continuous positive airway pressure treatment on left atrial volume and function in patients with obstructive sleep apnoea assessed by real-time three-dimensional echocardiography. Issue 22 (29th July 2009) - Oliveira, W; Campos, O; Cintra, F; Matos, L; Vieira, M L C; Rollim, B; Fujita, L; Tufik, S; Poyares, D
Abstract : Background: Obstructive sleep apnoea (OSA) has been reported as a predictor of left ventricle (LV) diastolic dysfunction and left atrium (LA) remodelling. The aim of this study is to evaluate the impact of OSA treatment with a continuous positive airway pressure device (CPAP) on the LA volume and function, as well as on the LV diastolic function. Methods: In total, 56 OSA patients were studied. All patients underwent real-time three-dimensional (RT3DE) and two-dimensional echocardiogram with tissue Doppler evaluation in order to estimate LA volumes, function and LV diastolic performance. A total of 30 patients with an apnoea-hypopnoea index greater than 20 were randomly selected to receive sham CPAP (n = 15) or effective CPAP (n = 15) for 24 weeks. They underwent echo examination on three different occasions: at baseline, after 12 weeks and 24 weeks of CPAP or sham CPAP. Results: In the effective CPAP group we observed the following changes from the baseline to the 24-week echo evaluation: (a) a reduction in the E/E′ ratio (10.3 (1.9) to 7.9 (1.3), p = 0.03); (b) an increase in the LA passive emptying fraction (28.8% (11.9%) to 46.8% (9.3%), p = 0.01); and (c) a reduction in the LA active emptying fraction (42.7% (11.5%) to 25.7 (15.7), p<0.01). In the sham group, there were no changes from the baseline to the 24-week echo. We found a positive correlation between 24 week/baseline LA active emptying volume and 24 week/baseline E/E′ ratios (r = 0.40, p<0.05) and a negative correlation between 24 week/baseline LA passive emptying volume and 24 week/baseline E/E′ ratios (r = −0.53, p<0.05). No significant changes were found on LA total emptying fraction. Conclusion: CPAP improved LV diastolic function and LA passive emptying, but not LA structural variables in OSA patients. Trial registration number: NCT00768807.